THE USE OF THE ANISOTROPY OF MAGNETIC REMANENCE IN THE RESOLUTION OF THE ANISOTROPY OF MAGNETIC SUSCEPTIBILITY INTO ITS FERROMAGNETIC AND PARAMAGNETIC COMPONENTS - Hrouda F. (My University, 2002)
The anisotropy of magnetic susceptibility (AMS) is often controlled by both ferromagnetic (sensu lato) and paramagnetic minerals. The anisotropy of magnetic remanence (AMR) is solely controlled by ferromagnetic minerals. Jelnek (Trav. Geophys. 37 (1993)) introduced a tensor derived from the isothermal AMR whose normalized form equals the normalized susceptibility tensor provided that the ferromagnetic fraction is represented by multi-domain magnetite. The present paper shows the close correlation between these tensors for a collection of strongly magnetic specimens containing multi-domain magnetite. In addition, acceptable correlation between the tensors was also found for a collection of specimens containing single-domain magnetite. A new method is developed for the AMS resolution into ferromagnetic and paramagnetic components using the AMR. Some examples are presented of this resolution in mafic microgranular enclaves in granodiorite and in gneisses of the KTB borehole.
Keywords: ANISOTROPY; SUSCEPTIBILITY; REMANENCE; COMPONENT RESOLUTION